2017
DOI: 10.1016/j.ijedudev.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The ERASMUS experience and its capacitating potential: Analysis of adaptive capabilities

Abstract: A B S T R A C TThis analysis takes as its focus the Erasmus experience and seeks to obtain information about how it contributes to human development in accordance with the capabilities approach of Amartya Sen and Marta Nussbaum. By way of a qualitative research proposal, and with the support of NVIVO 10 software, evidence is found of the "capacitating potential" of the aforementioned European Union mobility programme. This evidence is detailed through qualitative data-in this case regarding "adaptive capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…We computed a measure that subtracts ratings 'before Erasmus' to ratings 'after Erasmus' and, for all the groups of skills, the means are positive (Table 4), meaning that the 'after Erasmus' rating is on average higher than the 'before Erasmus' rating. This result is in line with previous studies on Erasmus studies who also found positive results as far as the development of skills is concerned (e.g., Bryla, 2015b;Dolga et al, 2015;Mart ınez-Usarralde et al, 2017;Vaicekauskas et al, 2013). Adaptability skills is the group where students perceive a higher development of skills.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We computed a measure that subtracts ratings 'before Erasmus' to ratings 'after Erasmus' and, for all the groups of skills, the means are positive (Table 4), meaning that the 'after Erasmus' rating is on average higher than the 'before Erasmus' rating. This result is in line with previous studies on Erasmus studies who also found positive results as far as the development of skills is concerned (e.g., Bryla, 2015b;Dolga et al, 2015;Mart ınez-Usarralde et al, 2017;Vaicekauskas et al, 2013). Adaptability skills is the group where students perceive a higher development of skills.…”
Section: Discussionsupporting
confidence: 92%
“…Results of this measure show that students clearly perceive that the exchange has a positive effect on their employability (Table 2). Although several authors have argued that Erasmus exchanges enhance the employability of students (Bryla, 2015a;Dolga et al, 2015;Mart ınez-Usarralde et al, 2017;Parey & Waldinger, 2011), to the best of our knowledge no previous study has measured employability from the perspective of Erasmus students.…”
Section: Discussionmentioning
confidence: 96%
“…Mobility is also connected with the pressure put on universities to equip graduates with skills to work in an international environment in response to the demand for employable university graduates (Leask, 2013 ). In the European context, mobility of HEI is associated with the Erasmus programme, which is perceived as “a strategic platform for the promotion of human development” (Martínez-Usarraldea, Pausá & García-López, 2017 , p. 107), establishing joint international research programmes and degrees. Mobility increases opportunities for educational experiences and international learning, therefore it is particularly an instrument for building the potential of individuals and societies.…”
Section: Internationalization Through Mobilitymentioning
confidence: 99%
“…These questions were formulated after an in-depth analysis of the literature containing the results of previous research on the educational dimension of students’ learning, virtual learning and international mobility (Tanhueco, Tanhueco-Nepomuceno, 2019 ; Cairns, 2018 ; Tran,, 2018 ; Martínez-Usarraldea, Pausá & García-López, 2017 ; Knight, 2015 ; Martin, 2017 ; Beelen & Jones, 2015 ; Messelink, Maele, Spencer-Oatey, 2015 ; Jacobone & Moro, 2015 ; Leask, 2013 ; Bennet, Maton & Kervin, 2008 ; Altbach & Knight, 2007 ; Karady, 2002 ) and finding that there is insufficient explanation for students learning in the virtual world through international mobility or foregoing explanations were built on the research carried out among students only, without taking into account other important “actors” in higher education such as academic teachers and mobility programme coordinators.…”
Section: Research Questionsmentioning
confidence: 99%
“…Despite the rapid expansion of international students worldwide and the growing concern for achieving the institutional improvements to support them, previous studies on this subject have been limited with regards to their scope and level of analysis. First, many studies have focused on cases involving English‐speaking countries or European countries as destinations for student mobility (Dvir & Yemini, ; Lee, ; Martínez‐Usarralde, Pausá, & García‐López, ). Few studies have examined non‐English‐speaking or economically emerging countries as destinations for inbound students (Ahmad & Buchanan, ; Jon, ).…”
Section: Introductionmentioning
confidence: 99%